Competição entre cooperativas de crédito e bancos em mercados locais - Souza, Fábio Augusto Pera de (2017)
This study evaluates competition between Brazilian Cooperative Financial Institutions (CFIs) and commercial banks in local credit markets running a pooled OLS of bank interest rate as a function of CFI market share, competition and county characteristics. Database has 55920 observations regarding the four quarters of 2013. Results show no significant impact of CFI presence on bank interest rates. On the other hand, bank type and Human Development Index (HDI) are important determinants of bank rates. It is necessary to look at relationship between CFIs and banks beyond traditional literature on banking competition. Moreover, regulators should not treat them the same way for empowering population should be a main goal of government.